PERANAN KOMUNIKASI PENDIDIKAN DALAM IMPLEMENTASI LITERASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) KELAS 3 - Nurmillah Laila Fitriyani; Venni Herli Sundi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research explores the role of educational communication in the implementation of literacy in the Pancasila student strengthening project in grade 3 of SDN Pondok Benda 02, as education in Indonesia faces challenges in integrating Pancasila values into the curriculum, particularly through the Pancasila Student Profile Strengthening Project (P5). Educational communication becomes a crucial aspect in ensuring that these values are understood and internalized by students. This study was motivated by the importance of effective communication in supporting the implementation of P5 literacy in grade 3, aiming to identify how educational communication can be strengthened to improve students' understanding of Pancasila. This study used descriptive qualitative methods, involving observation, interviews and document analysis. The research subjects included a grade 3 teacher and 15 students. Data were collected to understand the role of educational communication in supporting literacy related to P5, as well as identifying challenges faced in the process. The results showed that educational communication involving interactive approaches, the use of visual media, and group discussions significantly influenced students' understanding of Pancasila values. However, there are barriers such as lack of relevant resources and limited time allocated for literacy activities. Teachers play an important role in overcoming these challenges through creative and adaptive teaching strategies. The conclusion of this study is that effective educational communication is crucial in supporting the implementation of P5 literacy in grade 3.